Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve the equation for [tex][tex]$x$[/tex][/tex].

[tex]3(x + 2) = 2(2 - x)[/tex]

A. [tex]x = -2[/tex]
B. [tex]x = -\frac{2}{5}[/tex]
C. [tex]x = \frac{1}{2}[/tex]
D. [tex]x = 5[/tex]


Sagot :

Certainly! Let's solve the equation step by step:

Given equation:
[tex]\[ 3(x + 2) = 2(2 - x) \][/tex]

1. Distribute the coefficients to the terms inside the parentheses:
[tex]\[ 3 \cdot (x + 2) = 3x + 6 \][/tex]
[tex]\[ 2 \cdot (2 - x) = 4 - 2x \][/tex]
So, the equation becomes:
[tex]\[ 3x + 6 = 4 - 2x \][/tex]

2. Move all the terms involving [tex]\( x \)[/tex] to one side of the equation and the constant terms to the other side to solve for [tex]\( x \)[/tex]:
[tex]\[ 3x + 6 + 2x = 4 - 2x + 2x \][/tex]
Simplify both sides:
[tex]\[ 5x + 6 = 4 \][/tex]

3. Isolate the term with [tex]\( x \)[/tex] by subtracting 6 from both sides:
[tex]\[ 5x = 4 - 6 \][/tex]
Simplify the right-hand side:
[tex]\[ 5x = -2 \][/tex]

4. Solve for [tex]\( x \)[/tex] by dividing both sides by 5:
[tex]\[ x = \frac{-2}{5} \][/tex]

Therefore, the solution is:
[tex]\[ x = -\frac{2}{5} \][/tex]

Hence, the correct answer is:
B. [tex]\( x = -\frac{2}{5} \)[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.